STARTEGI KOMUNIKASI ORANG TUA DALAM UPAYA MENINGKATKAN ETIKA KOMUNIKASI PADA ANAK DI DESA PADANG PELASAN - Hurin Nabillah, Anisa; Riswanto, Riswanto (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2024)
Communication is a process where two or more people form or exchange information with each other and then it will be their turn to speak. Communication ethics is an attitude of politeness and respect towards other people and having good manners in speaking to someone. This research aims to determine parental communication in improving communication ethics among children in Padang Pelasan village. Researchers used qualitative methods and Joseph A Devito's theory as an analytical tool, divided into five, namely openness, empathy, support, positive feelings and equality. The results of the research show that openness, empathy, support, positive feelings and equality have been implemented and already exist, but the ethical changes that occur in children are factors in the friendship environment and also current technology, such as when children play games on smartphones and have online friends so there are negative impact on children's ethics. Keywords : Communication, Communication Ethics, Parents, Strategy